Selective recovery of heavy metals from wastewater by mechanically activated calcium carbonate: Inspiration from nature. (May 2020) - Wen, Tong; Zhao, Yunliang; Zhang, Tingting; Xiong, Bowen; Hu, Huimin; Zhang, Qiwu; Song, Shaoxian
Abstract: In nature, the calcium carbonate shows different interactions with different metal ions. Inspiration from this natural phenomenon, in this work, the selective recovery of heavy metals from wastewater by mechanically activated calcium carbonate was investigated. The changes in Ca 2+ concentration, pH value and metals uptake ratio of solution showed that M 2+ (M = Cu, Mn, Zn and Ni) were endowed with different migration rules, resulting in the various interaction with the calcium carbonate in metal-bearing solution. The combination of XRD, SEM, and stereomicroscope affirmed that the adsorbed M 2+ rarely change the lattice structure of calcium carbonate, while the adsorbed Cu 2+ and Zn 2+ could convert the mineral phase from calcium carbonate to posnjakite and hydrozincite, respectively. As a result of phase transition, 15% Cu 2+ and 6% Zn 2+ were uptaken with initial concentration of 1 mM for 100 min, however, the unsatisfactory recovery prevented the efficient recycling of metal. The mechanically activated calcium carbonate had a superior solubility at the solid/liquid interface, promoting mineral phase transformation on the premise of weak displacement adsorption. Hence, the uptake ratio of Cu 2+ and Zn 2+ were significantly increased to 99% and 53% at the same condition. Finally, Cu 2+ was recovered from polymetallic systems from complex environment with high precision. The concept of selective recycling in this research guides the development of innovative processes from natural information. Graphical abstract: Image 10804835 Highlights: CaCO3 adsorbs metals with little distortion of its lattice. Adsorbed Cu 2+ and Zn 2+ convert CaCO3 to posnjakite and hydrozincite. Mechanochemistry promotes mineral phase transition under weak adsorption. Selective recovery of Cu 2+ is achieved by mechanically activated CaCO3 .